Assessing the Impact of SM-3T on Enhancing Teacher Competence in 3T Areas: A Case Study in Indonesia - Budidarma, Ahmad; Rosyidi, Unifah; Susanto, Teguh Trianung Djoko (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v9i1.3146, 2024)
The Indonesian government has launched the Bachelor Program for Teaching in Frontier, Outermost, and Disadvantaged Areas (Indonesia: Sarjana Mendidik di Daerah Terdepan, Terluar, dan Tertinggal / SM-3T) as a means to enhance the educational standards in disadvantaged regions by deploying recent graduates as instructors. This study examines the impact of the SM-3T program on improving teacher competence in high-risk, remote, and underprivileged regions of Indonesia, namely in Terdepan, Terluar, and Tertinggal (3T) regions. This research is a qualitative case study approach, focus on teachers who took part in the program. Data were gathered using a blend of self-assessment forms and semi-structured interviews, offering valuable understanding of the professional growth of these educators, namely in their ability to teach effectively. According to the findings, the SM-3T program made a substantial contribution to enhancing teachers' pedagogical abilities, particularly in comprehending students' traits, devising and executing teaching methods, and doing assessments. The results emphasise the need of ongoing professional development initiatives in enhancing the effectiveness of education in remote regions. The research findings underline the importance of continuous assistance and training for teachers in 3T areas to guarantee enduring educational enhancements.